Waste Elimination via Suggestion Scheme in Aluminium Industry - Al-shehhi, Nawaf; Jamaludin, Khairur Rijal (Journal of Advanced Research in Business and Management Studies, 2020)
The main objectives of this explanatory research paper; first is to identify how the suggestion scheme is being utilized to reap the fruitful business results, plant performance and cost saving through lean concept, waste elimination, in the aluminium manufacturing industry based in UAE. The second objective is to explore the pathway of each suggestion by crossing different levels for approval and gets implemented. This study illustrates the experience of a single organization and the outcomes.